Effect of vibration during bulk and incremental filling on adaptation of a bulk-fill composite resin - Yung-Soo Kim; Seung-Ho Baek; Ryan Jin Young Kim (Scientific Reports, 2022)
Abstract This study evaluated the effect of vibration on adaptation of bulk-fill composite resin. A scanning laser doppler vibrometer measured the frequency and amplitude of a vibratory device (COMO; B&L Biotech) used for resin placement and visualized its effect on the resin according to depth. A bulk-fill composite resin (Filtek Bulk Fill; 3M ESPE) was placed in simulated cavities (4 mm diameter, 4 mm depth) by different layering methods (incremental filling with two 2-mm-thick layers vs. bulk filling with a single 4-mm-thick layer). The groups were further divided based on the application of vibration during restoration (no vibration vs. vibration). In addition to the surface void area at the cavity floor, the overall void volume and the void volumes of the bottom, middle, and top thirds were obtained for micro-computed tomography analysis. The frequency and amplitude of the COMO were approximately 149 Hz and between 26 and 51 µm, respectively. When vibration was not applied, incremental filling had a lower void volume in the bottom third of the cavity than did bulk filling (p < 0.05). Vibration applied with a 4-mm-thick bulk fill had no significant effect on the adaptation of composite resin (p > 0.05). In contrast, vibration reduced the amount of void formation in the bottom third of the cavity during incremental filling (p < 0.05). Application of vibration to resin with a 2-mm incremental-layering technique formed a smaller void at the interface between the cavity and resin and within the bulk-fill composite resin.